HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU KONSUMSI BUAH DAN SAYUR PADA SISWA KELAS V SDN 101866 KECAMATAN BATANG KUIS - Hasibuan, Noni; Dian Nila Sari, Fitri; Virginia Tamara, Chatrine; Nurlani, Siti; Suharsih (Jurnal Biogenerasi, 2024)
Elementary school age is a period of rapid growth and development, so the need for nutrients increases significantly. Balanced nutritional food intake is essential to ensure healthy and active child growth and development. One of the messages of balanced nutrition is to improve the consumption of fruits and vegetables by 300-400 grams (3-4 servings) per person per day. This study aims to determine the relationship between knowledge and attitudes towards fruit and vegetable consumption behavior in grade V students of SDN 101866, Batang Kuis District. This study is an observational study with a cross-sectional design, where the independent variables (knowledge and attitudes about fruit and vegetable consumption behavior) and the dependent variable (student behavior of fruit and vegetable consumption collected at the same time using 3 types of questionnaires, namely knowledge, attitude, and behavior questionnaires. The results of the study indicate that there is a relationship between knowledge and fruit and vegetable consumption behavior in Grade V Students of SDN 101866, Batang Kuis District with a p-value of 0.022 (<0.05) which means that knowledge reflects student behavior about fruit and vegetable consumption. There is a relationship between attitudes and fruit and vegetable consumption behavior with a p-value of 0.025 (<0.05) which means that students who have good attitudes are followed by good behavior by students about fruit and vegetable consumption. It can be concluded that good knowledge and attitudes of students will show good behavior about fruit and vegetable consumption.